Cooccurrence of anti-N-methyl-D-aspartate receptor encephalitis and COVID-19 infection – Case series of two patients with a brief review of literature - Mukherjee, Joydeep; Goyal, Sheetal; Arshad, Faheem; Nashi, Saraswati; Srijithesh PR,; Kulkarni, Girish Baburao; Alladi, Suvarna (Asian Journal of Medical Sciences, 2022)
Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is a clinical condition characterized by a myriad of psychiatric symptoms, abnormal movements, autonomic instability, seizures, and encephalopathy. Coronavirus disease-19 (COVID-19) infection is infrequently present with altered mental status. As the days of the COVID-19 pandemic pass, more and more awareness of its different types of immunological reactions are unveiled. A wide spectrum of clinical, pathological, and radiological manifestations has been reported. However, there have only been a few cases where anti-NMDAR antibodies have been found in people who have COVID-19. Herein, we reported two cases with simultaneous anti-NMDAR antibody and COVID-19 infection detection. Both cases clinically responded after treatment with an immunomodulator, showing significant improvement, and were discharged in a conscious and ambulatory state. Autoimmune encephalitis should be thought about if there are neurological symptoms associated with SARS-CoV-2 infection, and immunomodulators should be given to such patients.